The exploration of tactical urbanism as a strategy for adapting to climate change. The "SpaziAttivi" program in the city of Brescia - Boglietti, Stefania; Nota, Michela; Tiboni, Michela (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Lately, conventional urban planning strategies have encountered a new and often opposing force known as Tactical Urbanism, which has gained widespread prominence. This movement represents an approach to addressing issues at the neighborhood level, intervening in public spaces through citizen involvement and implementing temporary, cost-effective solutions. The Municipality of Brescia is actively exploring this innovative approach through the ’SpaziAttivi’ project, a component of the Climate Transition Strategy approved in 2021. This paper aims to elucidate why tactical urbanism has been chosen as the preferred method to enhance understanding, awareness, and the adoption of a collaborative approach to addressing climate change adaptation and mitigation issues. Specifically, the paper seeks to delineate the methodological process employed in selecting areas for tactical urbanism experiments, considering other successful participatory processes in Tactical Urbanism. The selection process ultimately leading to the decision to intervene in two areas, a significant reduction from the initial 56 proposals put forth by the citizens.